Easily biodegradable substrates are crucial for enhancing antibiotic risk reduction: Low-carbon discharging policies need to be more specified. (15th February 2022) - Zhang, Qifeng; Liu, Yang; Zhang, Chongjun; Zhou, Dandan
Highlights: Easily biodegradable substrates are crucial for antibiotic risk reduction. NaAc upregulated non-specific enzymes to improve antibiotic degradation. NaAc activated antioxidant enzymes and removed ROSs rapidly. Antibiotic detoxification and ROS removal decreased ARG production and transfer. NaAc reduced the opportunity of co-occurrence between ARGs and pathogens. Abstract: Governments have formulated stricter wastewater treatment plant (WWTP) discharge standards to address water pollution; however, with the cost of aggravating the refractory of the discharges. These policies are not in line with the classic co-metabolism theory; thus, we evaluated the effects of an easily biodegradable substrate on the removal efficiency of antibiotics and antibiotic resistance genes (ARGs) in the receiving water. In this study, reactor with 8 d of hydraulic retention time (HRT) was constructed to simulate a receiving river, and several antibiotics (0.30 mg/L each) were continuously discharged to the reactor (tetracycline, ciprofloxacin, amoxicillin, chloramphenicol, and sulfamethoxazole). Sodium acetate (NaAc) was used as a representative easily biodegradable substrate, and treatment protocols with and without a co-substrate were compared. The attenuation of the antibiotics in the simulated river and the production and dissemination of ARGs were analyzed. The results showed that 50 mg/L NaAc activated non-specific enzymes (a log2-fold change of 3.1–8.8 compared with 0 mg/L NaAc). The removal rate of the antibiotics was increased by 4–32%, and the toxicity of the downstream water was reduced by 35%. The upregulation of antioxidant enzymes caused the intracellular reactive oxygen species (ROSs) decreased by up to 47%, inhibiting horizontal gene transfer and reducing mobile genetic element-mediated ARGs (mARGs) by 18–56%. Furthermore, NaAc also increased the alpha diversity of the microbial community by 5–15% (Shannon-Wiener Index) and reduced the abundance of human bacterial pathogens by 22–36%. In summary, easily biodegradable substrates in the receiving water are crucial for reducing antibiotic risk. Graphical abstract: Image, graphical abstract